Acupuncture Resolving Old Controversies and Pointing New Pathways - Saad, Marcelo; de Medeiros, Roberta (IntechOpen, 2019)
Acupuncture may have about 4000 years of history, but it has only been clinically accepted in the West for some 40 years. Acupuncture receives both praise from its users and skepticism from its critics. High-quality scientific studies have advanced, but the technique of acupuncture in health services has stagnated. In this current scenario of contrasts, Acupuncture - Resolving Old Controversies and Pointing New Pathways intends to be a modern reference for scholars, without totally exhausting the subject. The editors expect this work to assist with the advancement of the scientific understanding and clinical usage of acupuncture. The authors are well versed in the subject and, along with literature reviews, are able to add their own impressions. In this book, some traditional fundamentals of ancient Asian medicine are translated into the current scientific knowledge of neurophysiology and mechanisms of action. Specific variations of acupuncture, such as the scalp microsystem technique, are discussed and explained. Practical aspects, such as education on acupuncture, are enriched with descriptions of novel treatments. The therapeutic use of acupuncture and related techniques is explored regarding their incorporation into a comprehensive integrative medicine approach. As editors, we thank the contributing authors for their exquisite work, and we congratulate IntechOpen for its efforts in book production. For you, the readers, we hope to match the trust you put in this work, and we hope you find it useful.